Association between polymorphism near the MC4R gene and cancer risk: A meta-analysis. Issue 36 (4th September 2020) - Zeng, Tian; Zhao, Jing; Kang, Yu; Wang, Xiaojiao; Xie, Hongjun
Abstract: Objective: Genome-wide association studies have identified single nucleotide polymorphisms (SNPs) near the melanocortin 4 receptor ( MC4R ), gene which are associated with risk of obesity. Since obesity is an established risk factor of cancer, several studies have examined the association between SNPs near the MC4R gene and cancer risk, but the findings are inconsistent. The present study aimed to perform a meta-analysis to clarify the association between SNPs near MC4R and cancer risk. Methods: The PubMed and Embase databases were searched for potentially eligible publications. All studies that evaluated the association between MC4R rs17782313 SNP (or its proxy rs12970134) and cancer risk were included. The pooled odds ratios with 95% confidence intervals (CIs) were calculated using the random-effects model. And subgroup analysis by cancer type (colorectal cancer, endometrial cancer and breast cancer) was conducted for further investigate the association. Results: A total of 6 eligible studies (6517 cases and 16, 886 controls) were included in the present meta-analysis. The results indicated that MC4R rs17782313 SNP was moderately associated with cancer risk (odds ratio = 1.12, 95% CI = 1.01–1.24). However, the subgroup analysis between different cancer types shows that rs17782313 is only associated with colorectal cancer but not the endometrial cancer and breast cancer. Risk factor in colorectal cancer was both significantly associated with rs17782313 with and without adjustment for body mass index; while the risk factor of the endometrial cancer and breast cancer were both not associated with the rs17782313 with and without adjustment for body mass index. There was no publication bias for the association between MC4R rs17782313 and cancer risk. Conclusion: The present meta-analysis confirmed the moderate association between MC4R rs17782313 and cancer risk.